Chemically gradient hydrogen-bonded organic framework crystal film - Mohammed, Abdul Khayum; Raya, Jesus; Pandikassala, Ajmal; Addicoat, Matthew A.; Gaber, Safa; Aslam, Mohamed; Ali, Liaqat; Kurungot, Sreekumar; Shetty, Dinesh (Angewandte Chemie-International Edition, 2023)
Hydrogen-bonded organic frameworks (HOFs) are ordered supramolecular solid structures, however, nothing much explored as centimetre-scale self-standing films. The fabrication of such crystals comprising self-supported films is challenging due to the limited flexibility and interaction of the crystals, and therefore studies on two-dimensional macrostructures of HOFs are limited to external supports. Herein, we introduce a novel chemical gradient strategy to fabricate a crystal-deposited HOF film on an in situ-formed covalent organic polymer film (Tam-Bdca-CGHOF). The fabricated film showed versatility in chemical bonding along its thickness from covalent to hydrogen-bonded network. The kinetic-controlled Tam-Bdca-CGHOF showed enhanced proton conductivity (8.3x10(-5) S cm(-1)) compared to its rapid kinetic analogue, Tam-Bdca-COP (2.1x10(-5) S cm(-1)), which signifies the advantage of bonding-engineering in the same system.
Keywords: Chemical Gradience; Crystal Films; Free-Standing Films; hydrogen-bonded organic framework; Interfacial Chemistry; proton conductivity

Salicylaldehydate coordinated two-dimensional-conjugated metal-organic frameworks - Mohammed, Abdul Khayum; Pena-Sanchez, Pilar; Pandikassala, Ajmal; Gaber, Safa; AlKhoori, Ayesha A.; Skorjanc, Tina; Polychronopoulou, Kyriaki; Kurungot, Sreekumar; Gandara, Felipe; Shetty, Dinesh (Chemical Communications, 2023)
A novel class of copper-based 2D-c-MOF was synthesized from 1,3,5-triformylphloroglucinol using green mechano-chemistry. Herein, metal coordination with the salicylaldehyde functional moiety was explored for the first time in MOFs. Moreover, an intrinsic semiconductive copper-based SA-MOF thin film was fabricated using an in situ salt-free method at room temperature.

Iron salicylaldehydate conjugated metal-organic framework for quasi solid-state supercapacitor - Mohammed, Abdul Khayum; Pandikassala, Ajmal; Sanchez, Pilar Pena; Gaber, Safa Abdullah; Canossa, Stefano; Kurian, Maria; Xavier, Gigi; He, Yao; Gandara, Felipe; Kurungot, Sreekumar; Shetty, Dinesh (CHEMICAL ENGINEERING JOURNAL, 2024)
Keywords: Carbon; conductivity; ELECTROLYTE CONCENTRATION; performance; ROBUST

MOFite: a high-density lithiophilic and scalable metal-organic framework anode for rechargeable lithium-ion battery - Gaber, Safa; Mohammed, Abdul Khayum; Javaregowda, Bharathkumar H.; Martinez, Jose Ignacio; Sanchez, Pilar Pena; Gandara, Felipe; Krishnamoorthy, Kothandam; Shetty, Dinesh (ANGEWANDTE CHEMIE-INTERNATIONAL EDITION, 2024)
Keywords: conjugated MOF; Energy storage; lithium ion battery; Metal-organic framework; scalable synthesis

Heteroatom-synergistic effect on anchoring polysulfides in chalcone-linked nanographene covalent organic frameworks for high-performance Li―S batteries - Ranjeesh, Kayaramkodath Chandran; Javaregowda, Bharathkumar H.; Gaber, Safa; Bhauriyal, Preeti; Kumar, Sushil; Skorjanc, Tina; Finsgar, Matjaz; Heine, Thomas; Krishnamoorthy, Kothandam; Shetty, Dinesh (Advanced Science, 2025)
Lithium-sulfur (Li & horbar;S) batteries are an attractive option for future energy storage devices because they offer higher theoretical specific capacity, energy density, and cost-effectiveness than commercial lithium-ion batteries. However, the practical applications of Li & horbar;S batteries are significantly limited by the shuttle effect caused by intermediate lithium polysulfides (LiPSs) and slow redox kinetics. In this study, the molecular engineering of chalcone-linked, sp(2)-bonded nanographene-type covalent organic frameworks (COFs) as sulfur hosts is reported to enhance interactions with LiPSs, thereby effectively suppressing the shuttle effect. The developed sulfur-hosting cathode material demonstrated outstanding battery performance, surpassing most reported materials by achieving a specific capacity of 1228 mA h g(-1) at 0.5C, with 80% retention after 500 cycles and an average Coulombic Efficiency (C.E.) of 99%. Additionally, the mechanisms of sulfur immobilization, the subsequent conversion into lithium polysulfides (LiPSs), and their binding energies with COFs are investigated using density functional theory (DFT) calculations. These findings offer valuable insights into the structure-property relationships essential for developing more efficient sulfur-hosting cathodes.
Keywords: anion-pi interaction; covalent organic frameworks; lithium-sulfur battery; nanographene; polysulfide shuttle